A "Grandiose Future for Italian Somalia": Colonial Developmentalist Discourse, Agricultural Planning, and Forced Labor (1900–1940)*. (10th November 2017) - Urbano, Annalisa
Abstract: This article explores the evolution of a developmentalist discourse for colonial Somalia and the attempts of the colonial government to present agricultural plans and labor policies as efforts to bring about social and economic development for colonial subjects and profit for colonial investors. In the long term, these efforts provided both a justification and a scope for the colonial venture. Fostering intensive farming and commercial agriculture, development planning institutionalized forced labor, disrupted the local production of foodstuff, and made the colony dependent on foreign imports.